IMU 451: Fiqh Muamalat. Case Study: Responsibility of Shariah Advisory in Islamic Finance / Norliana Abdullah … [et al.] - Abdullah, Norliana; Mohd Fadzil, Intan Batrisya; Abdul Aziz, Nurul Alwani; Mohd Azhari, Izzati Aina; Nazri, Muhammad Hafizuddin (2023)
Shariah officers are among the individuals responsible for ensuring that IKJ's activities and operations are always compliant Shariah requirements as stipulated in the Islamic Financial Services Act 2013 (IFSA 2013). However, IFSA does not specifically state the role and responsibilities of sharia officers, thus raising questions about the position in Islamic financial institutions. Therefore, this study is to analyze the Responsibility of Shariah Advisory In Islamic Finance. This study is qualitative which uses the document analysis method as a data collection method and the descriptive method as a data analysis method. The study found the concept of shariah advisory council, The duties and responsibilities of the Shariah Advisory Council (SAC) and the positive effects of the existence of a shariah advisory council. In general, the shariah advisory council plays an important role in finance in Malaysia, because Sharia Officers are people who carry out internal functions to ensure Sharia compliance. The task carried out is a heavy task because the task is a guide to the Shariah Committee to make it easier for JKS to carry out its responsibility to determine the level of shariah compliance.